Evaluation of the ovarian reserve in women and adolescent girls with Hashimoto's thyroiditis by serum anti-Müllerian hormone level: A systematic review and meta-analysis - Cui-juan Shi; Tian-rui Shao; Xudong Zhao; Bin Wang (Heliyon, 2023)
Objectives: Several researchers performed case-control studies to explore the relationship between Hashimoto's thyroiditis(HT) and ovarian reserve using anti-Müllerian hormone(AMH) in adolescent girls and women. But the results among these studies are inconsistent and the relationship between HT and ovarian reserve is still controversial. The study aimed to conduct the meta analysis of case-control studies to confirm the relationship between HT and ovarian reserve using AMH. Methods: 6 electronic databases including PubMed, EMBASE, the Cochrane Library, China National Knowledge Internet(CNKI), SinoMed and Wanfang were searched from inception to December 2021. Endnote X7.0 software was applied to managing all the relevant records. Then data extraction and evaluation of methodological quality of included studies were conducted after two-step selection.Review manager 5.4 version software and Stata 12.0 version software were used to perform all statistical analyses. Results: 10 case-control studies involving 1202 individuals were included in the present study. The preliminary results revealed AMH values were significantly higher in adolescent girls with euthyroid HT compared with healthy adolescent girls(MD = 1.97; 95%CI, 1.43–2.51; P < 0.001; I2 = 0%). The pooled results in the subgroup of female adults with euthyroid HT showed AMH values were not significantly different between patients with HT and healthy women(MD = −0.21; 95%CI, −0.51-0.09; P = 0.18; I2 = 38%). The pooled results in the two subgroups of female adults with subclinical hypothyroidism and overt hypothyroidism both showed AMH values were significantly lower in the HT group compared with healthy women [(MD = −0.60; 95%CI, −0.86 to −0.34; P < 0.001; I2 = 0%), (MD = −1.34; 95%CI, −1.94 to −0.74; P < 0.001; I2 = 65%)]. Conclusions: Ovarian reserve evaluated by serum AMH concentration is affected by female adults with subclinical hypothyroidism and overt hypothyroidism. The AMH level was significantly higher in euthyroid adolescent girls.